Proximity‐Induced Novel Ferromagnetism Accompanied with Resolute Metallicity in NdNiO3 Heterostructure. Issue 19 (11th August 2021) - Caputo, Marco; Ristic, Zoran; Dhaka, Rajendra S.; Das, Tanmoy; Wang, Zhiming; Matt, Christan E.; Plumb, Nicholas C.; Guedes, Eduardo B.; Jandke, Jasmin; Naamneh, Muntaser; Zakharova, Anna; Medarde, Marisa; et al.
Abstract: Employing X‐ray magnetic circular dichroism (XMCD), angle‐resolved photoemission spectroscopy (ARPES), and momentum‐resolved density fluctuation (MRDF) theory, the magnetic and electronic properties of ultrathin NdNiO3 (NNO) film in proximity to ferromagnetic (FM) La0.67 Sr0.33 MnO3 (LSMO) layer are investigated. The experimental data shows the direct magnetic coupling between the nickelate film and the manganite layer which causes an unusual ferromagnetic (FM) phase in NNO. Moreover, it is shown the metal–insulator transition in the NNO layer, identified by an abrupt suppression of ARPES spectral weight near the Fermi level ( E F ), is absent. This observation suggests that the insulating AFM ground state is quenched in proximity to the FM layer. Combining the experimental data (XMCD and AREPS) with the momentum‐resolved density fluctuation calculation (MRDF) reveals a direct link between the MIT and the magnetic orders in NNO systems. This work demonstrates that the proximity layer order can be broadly used to modify physical properties and enrich the phase diagram of RENiO3 (RE = rare‐earth element). Abstract : The ferromagnetic order in NdNiO3 (NNO) film is induced by the stray field from the La0.67 Sr0.33 MnO3 (LSMO) layer in proximity. Consequently, the magnetic coupling between the NNO film and the LSMO layer melts the metal–insulator transition in the NNO layer. Thus, this study illuminates the intimate connection between magnetic order and electronic properties in RENO.